2012
DOI: 10.1016/j.jcm.2011.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Chiropractic management of a patient with lumbar spine pain due to synovial cyst: a case report

Abstract: Introduction: The purpose of this study is to report the findings resulting from chiropractic care using flexion distraction spinal manipulation for a patient with low back and radicular pain due to spinal stenosis caused by a synovial cyst. Case Report: A 75-year-old man presented with low back pain radiating to the right anterior thigh and down the left posterior leg of 3 years' duration. Physical and imaging examinations showed a synovial cyst-induced spinal stenosis at the right L3-L4 level and bilateral L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…CLBP chronic low back pain LBP low back pain MCID minimal clinically important difference ODI Oswestry Disability Index manipulation [19][20][21][22][23][24][25][26] and flexion-distraction therapy [27][28][29][30][31][32][33][34][35][36][37][38][39][40] for the treatment of CLBP, [19][20][21][22][23][24][25][26] which are among the most common types of chiropractic manipulations used in practice 13 and are considered to be established treatments based on practice guidelines. 41 The decisions regarding the type(s) of care to use were made by 7 different licensed chiropractic physicians with at least 3 years of clinical experience, and all manipulations were administered by those physicians, whereas initial intake and ancillary care could have been provided by an intern.…”
Section: List Of Abbreviationsmentioning
confidence: 99%
“…CLBP chronic low back pain LBP low back pain MCID minimal clinically important difference ODI Oswestry Disability Index manipulation [19][20][21][22][23][24][25][26] and flexion-distraction therapy [27][28][29][30][31][32][33][34][35][36][37][38][39][40] for the treatment of CLBP, [19][20][21][22][23][24][25][26] which are among the most common types of chiropractic manipulations used in practice 13 and are considered to be established treatments based on practice guidelines. 41 The decisions regarding the type(s) of care to use were made by 7 different licensed chiropractic physicians with at least 3 years of clinical experience, and all manipulations were administered by those physicians, whereas initial intake and ancillary care could have been provided by an intern.…”
Section: List Of Abbreviationsmentioning
confidence: 99%
“…In their study, 50% of the lumbar and lower limb pain was relieved in 50% of the patients after an average of 15.95 days and 10.8 treatment sessions. Cox 12 ) reported that the VAS scores of patients with a lumbar herniated intervertebral disc and lumbar neuropathy improved after distraction manipulation therapy. Han 13 ) applied conservative therapy (oriental medicine) to lumbar spinal stenosis patients and stated that the patients reported decreased pain.…”
Section: Discussionmentioning
confidence: 99%